Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. -- From publisher's description. Contenu : Preface -- Acknowledgements -- About the author -- The study of gender -- Researching sex and gender -- Gender stereotypes: masculinity and femininity -- Hormones and chromosomes -- Theories of gender development -- Developing gender identity -- Intelligence and cognitive abilities -- Emotion -- Relationships -- Sexuality -- School -- Careers and work -- Health and fitness -- Stress, coping, and psychopathology -- Treatment for mental disorders -- How different? -- References -- Index.
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres